2007
DOI: 10.1016/j.biochi.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta mediates hepatocyte apoptosis through Smad3 generation of reactive oxygen species

Abstract: TGFβ induces hepatocyte apoptosis via reactive oxygen species (ROS) generation, the mitochondrial permeability transition (MPT), and caspase activation. The role of the Smad pathway in these events is unknown. In this study primary hepatocytes were isolated from Smad3 wild-type (+/+) and knockout (−/−) mice, and were treated with TGFβ (5 ng/ml) and/or trolox (2 mM). ROS generation, MPT, TGFβ-dependent transcription, and apoptosis were assessed in the presence or absence of Smad3 wild-type (WT) and dominant-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 23 publications
4
33
0
1
Order By: Relevance
“…We extend these observations further in the present study by showing that high glucosestimulated ROS generation by NADPH oxidase is dependent on extracellular TGF-␤ 1 . This agrees with the previously reported generation of ROS by TGF-␤ 1 through NADPH oxidase in lung fibroblasts and hepatocytes (4,5,36). The capacity of antisense p22 phox oligonucleotides to repress the effects of high glucose and TGF-␤ 1 on ROS levels confirmed NADPH oxidase as the target of TGF-␤ 1 in mesangial cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We extend these observations further in the present study by showing that high glucosestimulated ROS generation by NADPH oxidase is dependent on extracellular TGF-␤ 1 . This agrees with the previously reported generation of ROS by TGF-␤ 1 through NADPH oxidase in lung fibroblasts and hepatocytes (4,5,36). The capacity of antisense p22 phox oligonucleotides to repress the effects of high glucose and TGF-␤ 1 on ROS levels confirmed NADPH oxidase as the target of TGF-␤ 1 in mesangial cells.…”
Section: Discussionsupporting
confidence: 92%
“…TGF-␤ 1 strongly enhances reactive oxygen species (ROS) production by NADPH oxidase in fibroblasts and hepatocytes (4,5,36). While the mechanisms are incompletely defined, this effect may be mediated in part through Smadinduced increases in the expression of Nox4 or other NADPH oxidase subunits (4). It could also involve PKC isozymes.…”
mentioning
confidence: 99%
“…Consistent with these reports, we detected an increase in ROS generation 30 min after TGF-␤ stimulation in NHLFs (22)(23)(24). Using oxidant-sensitive fluorescent proteins localized to the mitochondria or cytosol, we were able to localize the source of these ROS to the mitochondria.…”
Section: Discussionsupporting
confidence: 90%
“…TGFb1 is the most effective apoptotic cytokine during hepatocarcinogenesis [22]. TGFb1 generated the reactive oxygen species and induced apoptosis of Huh-7 cells and activates first caspase-8, -9, and finally -3 [23,24]. Furthermore, a study on ''the loss of TGFb receptor'' showed that the hepatocytes in diethylnitrosamine and nodularin-induced-hyperplastic liver nodules escaped from the TGFb1-induced apoptosis and continued to proliferate [21].…”
Section: Introductionmentioning
confidence: 99%